AB0692 Belimumab in combination with azathioprine for remission maintenance in granulomatosis with polyangiitis and microscopic polyangiitis: effect on biomarkers. (12th June 2018) - Jayne, D.; Blockmans, D.; Luqmani, R.; Ji, B.; Green, Y.; Hall, L.; Roth, D.; Henderson, R.B.; Merkel, P.A.
Abstract : Background: GPA and MPA (related types of ANCA-associated vasculitis [AAV]) are organ-/life-threatening systemic vasculitides. B cells and increased circulating BLyS (a B cell survival factor) are implicated in AAV pathogenesis, suggesting a role for BLyS in these vasculitides. BEL is an anti-BLyS human immunoglobulin (Ig) G1λ monoclonal antibody. Objectives: Examine the effects of BEL plus azathioprine (AZA), on biomarkers in patients with AAV for remission maintenance following standard induction (IND) with glucocorticoids (GC) and CYC or RTX. Methods: This double-blind, placebo-controlled, multicentre study (BEL115466/NCT01663623 ) randomised (1:1) patients (≥18 years) with new/relapsing AAV following IND (oral or IV CYC or RTX), to AZA 2 mg/kg/day and oral GC, plus IV BEL 10 mg/kg or PBO (Days 0, 14, 28 and every 28 days until completion). Remission was defined as Birmingham Vasculitis Activity Score=0, plus GC ≤10 mg/day. The study was truncated after initiation (n~300 to~100) due to revised AAV standard of care (SoC) affecting recruitment. Biomarker endpoints (serum Igs, B cells and ANCA [anti-MPO/PR3]) were measured at baseline (BL) and thereafter. Summaries by IR were post hoc; no analyses were performed. Results: At BL, RTX patients had B cell counts≤LLQ. CYC patients had notably low BL B cell counts: the lowest were in oral-CYC patients. Circulating memory B cells (CD20+/CD27+) increased rapidly with BEL, then gradually returned to BL (CYC); no major changes occurred with PBO. BEL had no impact on the proportion of naïve CD20 +CD27− B cells vs PBO, post CYC IND. The number of RTX patients with quantifiable data was low; partial reconstitution occurred in a minority of patients (PBO 2/13; BEL 4/14) and did not translate into vasculitis relapses. Overall Ig levels declined more noticeably with BEL vs PBO; suggesting BEL affects antibody-secreting cells. ANCA+patients were similar between groups (PBO 32/50; BEL 30/49). No trends in change in ANCA status over time occurred, regardless of IR. Individual patient data showed no apparent trends between ANCA titres and AAV activity. Conclusions: Choice of IR for active AAV affects B cell dynamics. BEL pharmacodynamic effects occurred in patients with AAV receiving SoC. Given the small sample size and high variability, data must be interpreted with caution. Acknowledgements: Study funded by GSK. Sam Halliwell, PhD, Fishawack Indicia Ltd, UK, provided editorial assistance funded by GSK. Disclosure of Interest: D. Jayne Grant/research support from: GSK, Consultant for: GSK, D. Blockmans: None declared, R. Luqmani Grant/research support from: Arthritis Research UK, GSK, MRC, UCSF/OIF, Canadian Institutes of Health Research and The Vasculitis Foundation, Consultant for: Roche, GSK, Medpace and MedImmune, B. Ji Shareholder of: GSK, Employee of: GSK, Y. Green Shareholder of: GSK, Employee of: GSK, L. Hall Shareholder of: GSK, Employee of: GSK, D. Roth Shareholder of: GSK, Employee of: GSK, R. Henderson Shareholder of: GSK, Employee of: GSK, P. Merkel Grant/research support from: Actelion, Bristol-Myers Squibb, CaridianBCT, Celgene, ChemoCentryx, Genentech/Roche, GSK, Kypha, MedImmune/AstraZeneca, American College of Rheumatology, European League Against Rheumatism, National Institutes of Health (NHLBI, NIAMS, NIAID, NCATS, ORDR), US Food and Drug Administration, The Patient-Centred Outcomes Research Institute and The Vasculitis Foundation, Consultant for: Actelion, Alexion, Boston Pharm., Bristol-Myers Squibb, ChemoCentryx, Genzyme/Sanofi, GSK, Genentech/Roche, InflaRx, PrincipioBio, Proteon and Seattle Genetics